Study of Particle (Particulates Matter) Inside Ducting System : - Mustafa, Mohd Syafiq; Abd Hadi, Muhammad Isa (Progress in Engineering Application and Technology, 2020)
Air is very important in human life. Nowadays, the issue of Indoor Air Quality (IAQ) is relatively new in Malaysia. Environmental Protection Agency (EPA) stated that the Indoor Air Quality (IAQ) refers to the air quality within and around buildings and structures. In particular, it relates to the health and comfort of building occupants. By then, a comprehensive understanding of particle matters (PM) concentration in the HVAC system is essential to prevent and reduce contamination. Besides, this study is about the review of five previous researches in terms of the particle by gathering all information. Furthermore, the purposes of this study are to determine the significant standard, to compare the relevant standard requirement and to evaluate the method and result of duct cleanliness focusing on the particle from the previous study. It includes the comparison made between its method, results and standard. The comparison of standard is made based on the appropriate standard used in Malaysia due to IAQ condition and ducting cleanliness. Hence, the results show that majority of the researches under the category of medium cleanliness quality classes according to BS EN 15780 and the level of cleanliness are between ISO3 and ISO5.